ANALISIS PENGARUH GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI SMA NEGERI KOTA MADIUN 2013 - Chandra D., Christyani; Budi Wibowo, Satrijo; Murwani, Yuli (IKIP PGRI MADIUN, 2013)
Orientation: Headmasters play the most important role in the school. In every school, the headmaster has his own style in leading all of his teachers. The headmaster style itself often brings effect to the teachers. It is important to identify what kind of leadership style which is effective to increase the teachersâ performance in the school. This research analyzes the information about which kind of style that will make the teachersâ performance better.Research Purpose: This study aims to determine the effect of principal leadership style and organizational climate of schools on teacher performance in state senior high school in Madiun.Motivation for the study: This research provides various leadership styles having by headmasters in state senior high schools in Madiun. This may helps us in determining an effective style to be a leader.Reasearch design, Approach, and Method: This research uses quantitative approach to analyze the data. Â Variabel Â approach Â examined Â in Â this Â study include Â principal leadership style (X1), school organizational climate (X2), and teacher performance (Y).Main Findings: The results obtained in this study were: (1) the influence of principal leadership style on teacher performance in SMA Negeri Madiun percent higher, reaching 80.10%, (2) school organizational climate have an impact on teacher performance in SMA Negeri Madiun by 66.59%, (3) the principals leadership style and organizational climate schools together have an influence on teacher performance in SMA Negeri Madiun atÂ Â 80.10%.Â Â ThisÂ Â meansÂ Â thatÂ Â theÂ Â styleÂ Â ofÂ Â schoolÂ Â leadershipÂ Â andÂ Â school organizational climate has an influence on the performance of SMA Negeri Madiun.Contribution/Value-add: The result may helps another headmasters to have a better leadership style in order to get better performance from the teachers.